Digital empowerment for whom? An analysis of 'Network sovereignty' in low-income, rural communities in Mexico and Tanzania. Issue 14 (26th October 2022) - Parks, Lisa; Srinivasan, Ramesh; Aragon, Diego Cerna
ABSTRACT: When researchers invoke the term 'last billion' to refer to emerging ICT users, they often focus on network access as a 'solution' while neglecting important considerations such as local ownership or knowledge, both of which are essential to sustainable and empowering uses of these technologies in developing contexts. Research reveals that mere access to networks without active community involvement can fail to empower already marginalized and disenfranchized users. Building upon these findings, this article uses ethnographic methods to explore the meanings of 'network sovereignty' in rural, low-income communities in developing countries. It presents two case studies focused on local network initiatives in Oaxaca, Mexico and Bunda, Tanzania and then offers an assessment matrix to support future network sovereignty research based on five categories: community engagement; local cultures/ontologies; digital education and technological knowledge; economic ownership; and community empowerment. Our comparative research reveals that communities that are able to assert collective ownership over local infrastructure, embed network initiatives within local cultures, and prioritize digital education are much more likely to create and sustain local networks that support their economic, political, and cultural lives.